How cracks in SiOx-coated polyester films affect gas permeation - Yanaka, M; Henry, B; Roberts, A; Grovenor, C; Briggs, G; Sutton, A; Miyamoto, T; Tsukahara, Y; Takeda, N; Chater, R (2001)
In this paper theoretical models have been established that can account for the gas transmission through nanocomposite laminates, consisting of an oxide layer of finite permeability containing defects, on a polymer sheet of finite thickness. The defect shapes can either be in the form of long cracks or rectangular holes. The models offer a choice of exact numerical calculations or fast and intuitive analytical approximations. The experimental measurements of oxygen permeation through four different SiOx/poly(ethylene terephthalate) samples that were strained to produce distributions of cracks showed good agreement when compared with predicted results from the approximate analytic model. As a consequence of this observation, a key practical conclusion is that, because of the logarithmic dependence of transmission on the width of a crack, for a given strain it is better to have a small number of large cracks rather than a large number of small cracks. © 2001 Elsevier Science B.V. All rights reserved.